Evaluation of Preeclampsia Risk in Gestational Weight Gain - Dardan Baftiu; Erjona Abazaj; Ela Ali; Ledina Nikolla (European Scientific Journal, ESJ, 2022)
Background: The incidence of obesity worldwide has increased over the last 20 years. The increase in obesity in maternal pregnancy is causing a major challenge to obstetrics practices. The aimed study was to evaluate gestational weight gain as a risk for preeclampsia in pregnant women.  Methods: This cross-sectional study was conducted on 2756 pregnant women with gestational age≥37 weeks. The selection of women was categorized into two groups, 1528 normal-weight women with BMI less than 25kg/m2 and 1228 pregnant women with a BMI of 25kg/m2 or more. SPSS software version 26.0 was used to analyze data. Multivariate logistic regression described the relation of weight change to pregnancy course and outcomes. Results: A comparison between study groups shows an increase in antepartum complications in obese women. Besides that, arterial hypertension, pre-eclampsia, and gestational diabetes were more frequent in overweight women compared to normal-weight women. The incidence of cesarean was highest in overweight and obese women with a statistically significant difference from normal weight women (p-value <0.005). In addition, maternal overweight and obese were at twice the risk for delivering infants with macrosomia (OR = 3.1, 95%CI = [1.09-5.8]). The difference in mean birth weight of the babies between normal and overweight women was statistically significant (p<0.05). Conclusion: The results of this study show that obesity during pregnancy is associated with pregnancy complications. To optimize all complications for the mother and fetus, weight gain during the pregnancy must be controlled and appropriate. Furthermore, studies are recommended to explore maternal obesity complications and risk factors for obesity to minimize the adverse effect of this risk.